Multigrain rice instan sebagai pangan fungsional dengan tinggi protein dan serat panga: Multigrain Rice Instant as fungsional food with high protein and dietary fiber - Kurniawati, Elly; Nur Rochmah, Afrillia Vita (Politeknik Negeri Jember, 2024)
The objective of this research was to produce instant multigrain rice which has the potential as a functional food with high protein content, and as a source of dietary fiber. The design used in this study was a non-factorial Randomized Block Design (RBD), using 1 factor 5 treatments and 3 repetitions including F1 with concentrations (40% sorghum, 10% brown rice, 40% soybeans, 10% edamame) F2 (40% sorghum, 10% brown rice, 10% soybeans, 40% edamame) F3 (25% sorghum, 25% brown rice, 2 5% soybeans, 25% edamame) F4 (10% sorghum, 40% brown rice, 40% soybeans, 10% edamame) F5 (10% sorghum, 40% brown rice, 10% soybeans, 40% edamame). The analysis used in data processing is the ANOVA test followed by the Duncan test and analysis of the effectiveness index. The results showed that there was a significant effect on protein and dietary fiber content of several formulations. The resulting instant multigrain rice formulation has problems as a functional food, due to its high protein content and sufficient dietary fiber.